The influence of script-type cooperative learning model on student learning activities - Salong, Amjad (Harmoni Sosial: Jurnal Pendidikan IPS, 2023)
This study aimed to determine the effect of the learning model Cooperative Type Script Against Student Learning Activities. The method used in this study is an experimental research method using a research design experiment that aims to determine the difference in the increase in student learning activities who learn to use the Learning Model Cooperative Type Script (experimental class) with students who do not use conventional learning models (control class) in economics subjects, observations are used to see teacher activities and. This study's results indicate differences in student learning activities between the experimental class and the control class after doing the treatment. The experimental class uses a script-type cooperative learning model, and the control class uses a conventional method. This is shown in the results of the analysis. It can be seen that the value of tcount is greater than ttable or 2.717 > 2.002. This is following the Asymp. Sig. value of 0.009 which is less than the value of 0.05. So there are differences in student learning activities after treatment in the experimental and control classes.